Lightweight security architecture design for wireless sensor network - Chao WANG; Guang-yue HU; Huan-guo ZHANG (Tongxin xuebao)
Most previous security proposal did not consider key management or their authentication efficiency was very low.Lightweight security architecture and lightweight security algorithm were proposed for wireless sensor network,The problem of network encounters malicious nodes maybe occur in the procedure of backbone networks networking could be solved by threshold secret sharing mechanism.The lightweight ECC was proposed to optimize the CPK architecture based on normal ECC,authentication was efficient without the third-party CA,and could reduce the computational complexity,the key management could meet the resource limit in wireless sensor network,and the key security depended on the exponential computation complexity of the elliptic discrete logarithm decomposition.The scheme used the improved two-way authentication to ensure the communication security between common node and sink node,which could prevent man-in-the-middle attack.